2012
DOI: 10.1530/erc-12-0251
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative, genome-wide analysis of the DNA methylome in sporadic pituitary adenomas

Abstract: DNA methylation is one of the several epigenetic modifications that together with genetic aberrations are hallmarks of tumorigenesis including those emanating from the pituitary gland. In this study, we examined DNA methylation across 27 578 CpG sites spanning more than 14 000 genes in the major pituitary adenoma subtypes. Genome-wide changes were first determined in a discovery cohort comprising non-functioning (NF), growth hormone (GH), prolactin (PRL)-secreting and corticotroph (CT) adenoma relative to post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 36 publications
6
59
0
Order By: Relevance
“…[3,4,2,5] The relative contributions of these aberrations, their order of appearance, and the way in which their effects are manifest are largely unknown, however, specific aberration, be they genetic or epigenetic, are either common or particular to an adenoma subtype(s). [6,5,7] Moreover, the demarcation between genetic and epigenetic aberrations are perhaps less precise than initial findings suggested. In this context, we now know that the GNAS1 gene (the gsp oncogene), is activated or inappropriately expressed, either through mutation or relaxation of imprinting in growth hormone secreting pituitary adenomas.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[3,4,2,5] The relative contributions of these aberrations, their order of appearance, and the way in which their effects are manifest are largely unknown, however, specific aberration, be they genetic or epigenetic, are either common or particular to an adenoma subtype(s). [6,5,7] Moreover, the demarcation between genetic and epigenetic aberrations are perhaps less precise than initial findings suggested. In this context, we now know that the GNAS1 gene (the gsp oncogene), is activated or inappropriately expressed, either through mutation or relaxation of imprinting in growth hormone secreting pituitary adenomas.…”
Section: Introductionmentioning
confidence: 94%
“…PCR amplifications and pyrosequencing was performed as previously described by us. [6] Chromatin Immunoprecipitation (ChIP) analysis for histone modifications:…”
Section: Bisulphite Conversion and Pyrosequencingmentioning
confidence: 99%
“…Indeed, similar observations with respect to differences in the frequencies of methylation between high-and low-grade bladder tumors were first suggested by Ibragimova et al 47 Similar subtype and/or grade-associated differences have been reported in other tumor types including, pituitary, breast, and colon cancer subtypes. 37,48,49 In our analysis of NMIBC it remains unclear whether the increase in frequency and/or mean levels of methylation in the more aggressive tumors represents a more rapid accumulation of epigenetic changes during tumor progression, or reflects distinct epigenetic pathways of tumor development and outgrowth. 50,51 Our findings may therefore reflect either of the described scenarios in the more aggressive (high-grade) tumors and suggests that these tumors are either consequent to progression from low-intermediategrade tumors, or are the progeny of aberrations in distinct epigenetic pathways within these NMIBC subtypes.…”
Section: Discussionmentioning
confidence: 95%
“…34,35,36 These analyses also showed that for the majority of regions investigated, methylation extended to include contiguous promoter-associated CpG sites. On the basis of previous reports from our own and other groups, 37,38 we employed stringent criteria (b-value differences 0.4) to identify differentially methylated genes across multiple CpG sites; such criteria are more consistently associated with bona fide changes in methylation, and are more likely to show associations with gene expression. 37,39,40,41 The analysis of the discovery cohort of high-grade NMIBC identified 1,057 CpGs, across 256 gene-promoter-associated CpG islands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation